Inhibition of transforming growth factor β-activated kinase 1 prevents inflammation-related cartilage degradation in osteoarthritis - Cheng, Jin (Sci Rep, 2016)
Osteoarthritis (OA) is a common debilitating joint disorder, there’s still no available disease-modifying drug for OA currently. This study aims to explore the role of TAK1 in OA pathogenesis and therapeutic efficiency of TAK1 inhibition for OA. The contribution of TAK1 to OA pathogenesis was investigated by intra-articular injection of TAK1-encoding adenovirus in rats. TAK1 inhibitor 5Z-7-induced expression changes of extracellular matrix (ECM)-related genes were detected by real-time PCR. The protective effect of 5Z-7 against OA progression was evaluated in a post-traumatic OA rat model. Our results showed that intra-articular injection of Ad-Tak1 induced cartilage destruction and OA-related cytokine secretion in rat joints. TAK1 inhibition by 5Z-7 efficiently blocked NF-κB, JNK and p38 pathways activation in OA chondrocytes and synoviocytes, Meanwhile, 5Z-7 significantly decreased the expression of matrix-degrading enzymes and pro-inflammatory cytokine, while increased ECM protein expression, which are all crucial components in OA. 5Z-7 also ameliorated ECM loss in OA cartilage explants. More importantly, 5Z-7 significantly protected against cartilage destruction in a rat model of OA. In conclusion, our findings provide the first in vivo evidence that TAK1 contributes to OA by disrupting cartilage homeostasis, thus represents an ideal target for OA treatment, with 5Z-7 as a candidate therapeutic.